2008
DOI: 10.1590/s0100-204x2008000900007
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heterosis in common bean cultivars

Abstract: -The objective of this work was to determine the combining ability and heterosis, for productivity and yield components, in diallel hybrids derived from crossings between BRSMG-Talismã, IPR Uirapuru, FT Soberano, BRS Campeiro, IAC Tybatã, and IPR Juriti parent cultivars. Fifteen hybrids were generated from diallel crosses, excluding reciprocals. The general and specific combining abilities were significant for plant height, number of pods per plant, number of seeds per plant, number of seeds per pod, 50-seed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
(22 reference statements)
1
11
0
1
Order By: Relevance
“…Krause et al (2012) also found a positive effect of gi for plant height for IAC Carioca Tybatã under field conditions. Gonçalves-Vidigal et al (2008) registered the occurrence of additive and non-additive effects under irrigated conditions for plant height, number of pods per plant, number of seeds per plant, number of seeds per pod, average weight of 50 seeds and grain yield, besides reaching similar results for the cultivar IAC Carioca Tybatã, which showed negative effects of ĝ i for yield and weight of seeds and positive effects of g i for plant height.…”
Section: Resultsmentioning
confidence: 60%
“…Krause et al (2012) also found a positive effect of gi for plant height for IAC Carioca Tybatã under field conditions. Gonçalves-Vidigal et al (2008) registered the occurrence of additive and non-additive effects under irrigated conditions for plant height, number of pods per plant, number of seeds per plant, number of seeds per pod, average weight of 50 seeds and grain yield, besides reaching similar results for the cultivar IAC Carioca Tybatã, which showed negative effects of ĝ i for yield and weight of seeds and positive effects of g i for plant height.…”
Section: Resultsmentioning
confidence: 60%
“…In this case, the superiority of the sum of squares of SCA was observed for GCA (Table 3). Predominance of non-additive effects associated with grain yield and plant height in common bean was also found by Gonçalves-Vidigal et al (2008). Also studying GCA and SCA in segregating F 2 populations derived from a complete diallel, Machado et al (2002) observed predominance of SCA for grain yield.…”
Section: Methodsmentioning
confidence: 78%
“…These results suggest that the heterotic effects detected in F 2 are small. The predominance of dominance effects associated with grain yield in common bean was reported by Rodrigues et al (1998) and Gonçalves-Vidigal et al (2008). However, other studies reported predominantly additive effects for YLD (Santos et al 1985, Kurek et al 2001).…”
Section: Resultsmentioning
confidence: 95%